Conflict Resolution of Rules Assigning Values to Virtual Attributes - Ioannidis, Yannis E; Sellis, Timos K (University of Wisconsin-Madison Department of Computer Sciences, 1989)
In the majority of research work done on logic programming and deductive databases, it is assumed that the set of rules defined by the user is consistent, i.e., that no contradictory facts can be inferred by the rules. In this paper, we address the problem of resolving conflicts of rules that assign values to virtual attributes. We devise a general framework for the study of the problem, and we propose an approach that subsumes all previously suggested solutions. Moreover, it suggests several additional solutions, which very often capture the semantics of the data more accurately than the known approaches. Finally, we address the issue of how to index rules so that conflicts are resolved efficiently, i.e. only one of the applicable rules is processed at query time.